Burma Terrane Collision and Northward Indentation in the Eastern Himalayas Recorded in the Eocene‐Miocene Chindwin Basin (Myanmar). Issue 10 (21st October 2020) - Westerweel, Jan; Licht, Alexis; Cogné, Nathan; Roperch, Pierrick; Dupont‐Nivet, Guillaume; Kay Thi, Myat; Swe, Hnin Hnin; Huang, Huasheng; Win, Zaw; Wa Aung, Day
Abstract: The Burma Terrane (Myanmar) played an important role in the India‐Asia collision and moved over 2, 000 km northward on the Indian Plate during the Cenozoic, before colliding with the Asian margin. However, the timing of this collision and its correlation to regional uplift phases, sedimentary provenance, and basin development remain poorly constrained. We report sedimentological, paleomagnetic, and geochronological data from the late Eocene to early Miocene strata of the Chindwin Basin in the Burmese forearc, constraining the paleogeographic evolution of the Burma Terrane and the Eastern Himalayan orogen. Our results highlight two unconformities of late Eocene‐middle Oligocene and latest Oligocene‐early Miocene age, revealing a two‐stage interaction of the Burma Terrane with the Asian margin during its northward translation. The first unconformity follows rapid ~0.6 m/ky subsidence in the Burmese forearc, as shown by magnetostratigraphy. The transition to a fluvial depositional environment and the occurrence of reworked sediments at this first unconformity likely records the commencing collision of India and the northern extent of the Burma Terrane with the Asian margin. The second unconformity shows drastic changes in magnetic properties, mineralogy, and provenance, with high‐grade metamorphic grains and early Miocene apatite U‐Pb and fission‐track ages indicating that it is coeval to a major deformation phase in Myanmar and the Eastern Himalayan orogen. It likely records the indentation of the Burma Terrane into the Eastern Himalayan collision zone, forming the modern Eastern Himalayan Syntaxis. Plain Language Summary: The evolution of the India‐Asia collision and the resulting formation of the dramatic Himalayan mountain chain are highly debated among geologists. One of the reasons is that the easternmost extent of this mountain range is understudied compared to its central part. In Myanmar, at the eastern end of the Himalayas, this is partly caused by political and scientific isolation over the past 70 years, limited road access, and jungle covering much of the exposure. This study helps to constrain the paleogeographic evolution of the Burma Terrane, the microplate including most of Myanmar. To this end, we used a variety of methods including describing sedimentary deposits of the Burma Terrane, dating these deposits and determining their corresponding source regions. With this new information, we were able to determine that the deposition of these sediments occurred from ~40 to 23 million years ago but was discontinuous with two large hiatuses of millions of years long. Our results show that these two hiatuses are a consequence of a two‐stage process during the large northward motion of the Burma Terrane involving (1) the first collision of India and the northern Burma Terrane with Asia and (2) the indentation of Burma into the Himalayan collision zone. Key Points: The Eocene to Lower Miocene sedimentary infill of the Chindwin forearc basin of the Burma Terrane is punctuated by two major unconformities The first late Eocene‐middle Oligocene unconformity records the initial collision of India and the northern Burma Terrane with Asia The second late Oligocene‐early Miocene unconformity marks major deformation in the Eastern Himalayas due to Burma Terrane northward motion